2011
DOI: 10.1007/s11060-011-0584-7
|View full text |Cite
|
Sign up to set email alerts
|

HMME-based PDT restores expression and function of transporter associated with antigen processing 1 (TAP1) and surface presentation of MHC class I antigen in human glioma

Abstract: Numerous studies have established that photodynamic therapy (PDT) can trigger tumor-specific immunity and cancer cell immunogenicity, both of which play a critical role in the long-term control of oncogenesis; however, the underlying mechanisms are largely unexplained. Deficiency of the transporter associated with antigen processing 1 (TAP1) has been observed in a variety of tumors, and the question has been raised whether the restoration of TAP1 could facilitate the activation of antitumor immunity. To elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Therefore, upregulation of MHCI is viewed as a therapeutic goal in many types of tumors [2931]. Similar to plasma, photodynamic therapy uses oxygen radicals and was shown to restore MHCI expression in human glioma [32]. Along similar lines, radiation upregulates MHCI expression in the breast [33], lung [34], and colon cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, upregulation of MHCI is viewed as a therapeutic goal in many types of tumors [2931]. Similar to plasma, photodynamic therapy uses oxygen radicals and was shown to restore MHCI expression in human glioma [32]. Along similar lines, radiation upregulates MHCI expression in the breast [33], lung [34], and colon cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…The work of Zhang et al showed that PDT may have this ability. They showed that HMME-PDT enables glioma cells to recover both the expression of functional TAP1 and the presentation of MHC class I surface antigens [202]. However, this is the only report in the field so far, so it needs to be confirmed in other works.…”
Section: Transporter Associated With Antigen Processingmentioning
confidence: 92%
“…provided evidence that PDT also induces presentation of surface MHC I related antigens and enhances antigen processing through the restoration of TAP1 protein expression in glioma cells ( 163 ). TAP1 can potentiate the transport of new antigen peptides and therefore is involved in PDT-related immunomodulation ( 163 ). The generation of ROS plays a significant role in PDT-induced immunity ( 160 ).…”
Section: Physical Methods and Their Mechanismsmentioning
confidence: 99%